Access to history for the IB diploma : causes, practices, and effects of wars - Dailey, Andy (London : Hodder Education, 2013)
Ensure your students have access to the authoritative, in-depth and accessible content of this series for IB Diploma History.
Keywords: century. War -- Causes; Military history, -- Examinations -- Study guides; Modern -- 20th century; Military history, Modern -- 20th